In Silico Prediction of Horizontal Gene Transfer Events in Lactobacillus bulgaricus and Streptococcus thermophilus Reveals Protocooperation in Yogurt Manufacturing - Liu, Mengjin (American Society for Microbiology (ASM), 2009)
Lactobacillus bulgaricus and Streptococcus thermophilus, used in yogurt starter cultures, are well known for their stability and protocooperation during their coexistence in milk. In this study, we show that a close interaction between the two species also takes place at the genetic level. We performed an in silico analysis, combining gene composition and gene transfer mechanism-associated features, and predicted horizontally transferred genes in both L. bulgaricus and S. thermophilus. Putative horizontal gene transfer (HGT) events that have occurred between the two bacterial species include the transfer of exopolysaccharide (EPS) biosynthesis genes, transferred from S. thermophilus to L. bulgaricus, and the gene cluster cbs-cblB(cglB)-cysE for the metabolism of sulfur-containing amino acids, transferred from L. bulgaricus or Lactobacillus helveticus to S. thermophilus. The HGT event for the cbs-cblB(cglB)-cysE gene cluster was analyzed in detail, with respect to both evolutionary and functional aspects. It can be concluded that during the coexistence of both yogurt starter species in a milk environment, agonistic coevolution at the genetic level has probably been involved in the optimization of their combined growth and interactions.